Bacteriological research and 'puerperal' fever: female health and childbirth in late colonial India - Bajpayee, Kaushalya (Medical history, 2025)
This article explores female healthcare at the crossroads of bacteriology and obstetric research. Puerperal fever or childbed fever manifested as an epidemic since the nineteenth century, and in both Europe and America, it charted a distinct course for bacteriological research. With the identification of bacteriological causes, new sets of public health regimes were instituted in both regions. The experience of the colonies, however, differed. This paper focusses on how colonial discourse on obstetric nursing, midwifery, clinical hygiene, and maternal healthcare can be positioned in this global history of female health research. The paper explores why, in India, on one hand, bacteriological research in female health suffered in terms of priority (unlike that of cholera and plague) despite the alarming rate of maternal mortality. On the other hand, medical practitioners trained in Europe worked as the conduit through which the bacteriological research of Europe made its way into India. Contemporary documents reveal how colonial prerogatives were channeled through the race theories linked to Indian cultural practices related to midwifery and obstetric nursing, and how the female health discourse was still marred by the notion of tropicality.